Long-term outcome after radiotherapy in patients with atypical and malignant meningiomas: clinical results in 85 patients treated in a single institution leading to optimized guidelines for early radiation therapy - Adeberg, Sebastian; Hartmann, Christian; Welzel, Thomas; Rieken, Stefan; Habermehl, Daniel; Deimling, Andreas von; Debus, Jürgen; Combs, Stephanie (International journal of radiation oncology, biology, physics, 2012)
Purpose Previously, we could show that the new World Health Organization (WHO) classification of meningiomas significantly correlated with outcome in patients with atypical and anaplastic histology. In the present work, we analyzed our long-term experience in radiotherapy for atypical and malignant meningioma diagnosed according to the most recent WHO categorization system. Patients and Methods Sixty-two patients with atypical and 23 patients with malignant meningioma have been treated with radiotherapy. Sixty percent of all patients received radiotherapy (RT) after surgical resection, 19% at disease progression and 8.3% as a primary treatment. Radiation was applied using different techniques including fractionated stereotactic RT (FSRT), intensity-modulated RT, and combination treatment with carbon ions. The median PTV was 156.0 mL. An average dose of 57.6 Gy (range, 30-68.4 Gy) in 1.8-3 Gy fractions was applied. All patients were followed regularly including clinical-neurological follow-up as well as computed tomographies or magnetic resonance imaging. Results Overall survival was impacted significantly by histological grade, with 81% and 53% at 5 years for atypical or anaplastic meningiomas, respectively. This difference was significant at p = 0.022. Eighteen patients died of tumor progression during follow-up. Progression-free survival was 95% and 50% for atypical, and 63% and 13% for anaplastic histology at 2 and 5 years. This difference was significant at p = 0.017. Despite histology, we could not observe any prognostic factors including age, resection status, or Karnofsky performance score. However, preexisting clinical symptoms observed in 63 patients improved in 29.3% of these patients. Conclusion RT resulted in improvement of preexisting clinical symptoms; outcome is comparable to other series reported in the literature. RT should be offered after surgical resection after initial diagnosis to increase progression-free survival as well as overall survival. Novel clinical concepts are under investigation to further improve outcome in patients with high-grade meningiomas.
Available online 2 December 2011
Gesehen am 23.04.2018
This work was presented in part at the Annual Meeting of the German Society of Radiation Oncology (DEGRO), June 2010, Wiesbaden, Germany